Tertiary Chiral Nanostructures from C−H⋅⋅⋅F Directed Assembly of Chiroptical Superatoms. Issue 41 (1st September 2021) - Shen, Hui; Xu, Zhen; Wang, Lingzheng; Han, Ying‐Zi; Liu, Xianhu; Malola, Sami; Teo, Boon K.; Häkkinen, Hannu; Zheng, Nanfeng
Abstract: We report the synthesis and structure of tertiary chiral nanostructures with 100 % optical purity. A novel synthetic strategy, using chiral reducing agent, R and S‐BINAPCuBH4 (BINAP is 2, 2′‐Bis(diphenylphosphino)‐1, 1′‐binaphthyl), is developed to access to atomically precise, intrinsically chiral [Au7 Ag6 Cu2 (R‐ or S‐BINAP)3 (SCH2 Ph)6 ]SbF6 nanoclusters in one‐pot synthesis. The clusters represent the first tri‐metallic superatoms with inherent chirality and fair stability. Both metal distribution (primary) and ligand arrangement (secondary) of the enantiomers exhibited perfect mirror images, and unprecedentedly, the self‐assembly driven by the C−H⋅⋅⋅F interaction between the phenyl groups of the superatom moieties and SbF6 − anions induced the formation of bio‐mimic left‐ and right‐handed helices, achieving the tertiary chiral nanostructures. DFT calculations revealed the connections between the molecular details and chiral optical activity. Abstract : Tertiary chiral nanostructures have been created by assembling chiroptical superatoms of [Au7 Ag6 Cu2 ( S ‐ or R ‐BINAP)3 (SCH2 Ph)6 ] + (BINAP=2, 2′‐bis(diphenylphosphino)‐1, 1′‐binaphthyl). Both metal framework (primary structure) and surface ligands (secondary) of the nanocluster display perfect mirror symmetry. C−H⋅⋅⋅F hydrogen bonding between the clusters and SbF6 − counterions direct formation of left‐ or right‐handed helices.